Effects of nutritional stress on soil fertility and antioxidant enzymes of rice in different growth periods - Cai, Qiuliang; Zou, Yi; Zhong, Ning; Jia, Guikang (Frontiers in Plant Science, 2024)
Stress in plants denotes the detrimental impact of alterations in external environmental conditions on regular plant growth and development. Plants employ diverse mechanisms to mitigate or evade nutritional stressinduced damage. In order to investigate the physiological response mechanism of plants to nutritional stress and assess its impact on soil nutrient content and antioxidant enzyme activity in rice, a field experiment was conducted applying five treatments: control, nitrogen (N) deficiency, phosphorus (P) deficiency, potassium (K) deficiency, and full fertilization. Rice leaf and soil samples were concurrently gathered during both the vegetative and reproductive growth stages of rice. Analysis was conducted on soil N, P, and K levels, as well as leaf antioxidant enzyme activities, to investigate the impact of nutrient stress on rice antioxidant enzymes and soil fertility. The research findings indicate that full fertilization treatment enhanced the agronomic properties of the soil compared to the control treatment. In the N-deficiency treatment, reactive oxygen species (ROS) levels increased by 16.53-33.89% during the reproductive growth period compared to the vegetative growth period. The peroxidase (POD) activity decreased by 41.39% and superoxide dismutase (SOD) activity increased by 36.22% under K-deficiency treatment during the reproductive growth period compared to the vegetative growth period. Consequently, applying N and P fertilizer during the vegetative growth period can decrease membrane lipid peroxidation levels by 7.34-72.53%. The full fertilization treatment markedly enhanced rice yield compared to other treatments and increased the Nitrogen activation coefficient (NAC) and Phosphorus activation coefficient (PAC) in the soil, while decreasing the PAC. Elevating NAC levels can stimulate the activity or content of PRO, MDA, and RPS during the vegetative growth stage, whereas in the reproductive growth stage, it will decrease the content of ROS, PRO, and MDA. This data offers valuable insights and theoretical support for nutritional stress research.